Pengendalian Penyakit Karat Daun Kopi dengan Ekstrak Teh Hitam - Christanti Sumardiyono; Setyo Agung (Jurnal Perlindungan Tanaman Indonesia, 1996)
The research was done to know the efficacy of black tea extract to control coffee leaf rust, the most important disease of Arabica coffee caused by the fungus Hemileia vastatrix B et Br. Black tea was extracted by boiling 50 g of tea in 500 ml of water until 50 ml of solution was left and used as spraying material after 10 time dilution. Influence of black tea extract to urediospores germination was done by spore germination technique. Field experiment was done at Pagilaran Tea Plantation with a susceptible Arabica coffee Kate 26 variety. Coffee plants was sprayed with diluted tea extract eight times with 10 days interval and 0,3% of triadimefon was used as standart fungicide. The result showed that black tea extract inhibited germination of urediospora and reduced germtube length up to 10-4 dilution. The extract of black tea could reduce disease intensity of coffee leaf rust in the field better than triadimefon. Ten days after first spraying, disease intensity was reduced but it increased after 5 times spraying. After 8 times spraying disease intensity on coffee tree sprayed with the black tea extract was lower than that sprayed with tradimefon.